Aluminum hydroxide-mediated synthesis of mesoporous metal oxides by a mechanochemical nanocasting strategy. Issue 40 (7th October 2019) - Liu, Jixing; Cheng, Huifang; Bao, Jiafeng; Zhang, Pengfei; Liu, Miaomiao; Leng, Yan; Zhang, Zihao; Tao, Runming; Liu, Jian; Zhao, Zhen; Dai, Sheng
Abstract : A mechanochemical nanocasting strategy using aluminum hydroxide as the mesoporous structure-directing agent to fabricate mesoporous metal oxides. Abstract : Mesoporous metal oxides (MOs) have attracted significant interest in heterogeneous catalysis due to their wide pore size distribution and high pore volume. Herein, we present a facile mechanochemical nanocasting strategy using aluminum hydroxide as the mesoporous structure-directing agent, which overcomes the drawbacks associated with wet template-assisted methods. In this procedure, by simply grinding a mixture of commercial aluminum hydroxide and MO precursors, a series of mesoporous MOs with high specific surface areas and narrow pore size distributions have been constructed in a short time ( e.g., Fe2 O3, 280 m 2 g −1 ; Co3 O4, 155 m 2 g −1 ; CeO2, 192 m 2 g −1 ; ZrO2, 170 m 2 g −1 ; CuO x –CeO y, 177 m 2 g −1 ; FeO x –CeO y, 170 m 2 g −1 ; CoO x –CuO y –CeO z, 154 m 2 g −1 ; CoO x –FeO y –CeO z, 133 m 2 g −1 ). It is expected that this strategy may open up new opportunities for fabricating a number of advanced porous materials with abundant porosity in the near future.